The Disadvantaged Child’s Negotiation of the Dimensions of Time, Space and Relationality in an Elite Private School - Srivastava, Deepti (JOURNAL OF INDIAN EDUCATION, 2014)
This article explores the narrative experiences of a disadvantaged child in an elite private school. It problematises the ‘deep structure’ of the school and explains how the child negotiates them in order to learn. Looked at from the dimensions of time, space and relationality, as proposed by Reay, it draws attention to the need to acknowledge the identity of the child to make teaching-learning more sensitive, responsive and meaningful.